Impact of the SARS-CoV-2 Delta Variant on the Psychological States and Health-Related Quality of Life in Patients With Crohn’s Disease - Li, Jiajia; Sun, Yunyun; Hu, Xiaolin; Zhao, Tiantian; Yao, Guanghuai; Xiao, Weiming; Ding, Yanbing; Hou, Sicong; Wang, Mei (Frontiers in Medicine, 2022)
Background: Since the outbreak of the coronavirus disease 2019 (COVID-19) pandemic first reported in Wuhan, China, several research on the psychological impact of the pandemic on patients with Crohn’s disease (CD) have been conducted. However, with the progression of the global pandemic and the emergence of the SARS-CoV-2 B.1.617.2 (Delta) variant, follow-up studies need to be performed to monitor the alterations of psychological status and health-related quality of life (HRQoL) among CD patients. Aims: We aimed to evaluate the impact of the SARS-COV-2 Delta variant on the mental health and life quality among the CD population and tried to explore potent risk factors. Methods: This observational study included 153 CD patients who responded to our pre-designed self-reported questionnaire. Demographic, clinical and psychological information were collected and analyzed. Results: Quite a number of CD patients were confronted with different levels of anxiety and depression, with incidence of 28.10% and 31.37% for anxiety and depression, respectively. Compared with nonpandemic circumstances, the life quality of CD patients due to the present situation was more often compromised. Isolation (OR: 4.71, P = 0.007) was verified as a risk factor for anxiety while use of telemedicine could help relieve anxiety (OR: 0.22, P <0.001). Worsening of symptoms (OR: 4.92, P = 0.006), isolation (OR: 5.75, P = 0.005), and drug withdrawn (OR: 2.66, P = 0.026) were identified to be independent factors for developing depression. Likewise, use of telemedicine (OR: 0.13, P <0.001) was negatively related to depression. Considering life quality, vaccination (OR: 3.07, P = 0.021) together with no medication (OR: 7.73, P = 0.010) was relevant to better life quality while worsening of symptoms (OR: 0.09, P = 0.034) were an independent risk factor for impaired life quality. Conclusions: Many CD patients suffered from symptoms of anxiety and depression and impaired life quality during the COVID-19 pandemic. Those in isolation or with worsening of symptoms and drug withdrawn were more prone to experience psychological stress. Individualized management such as drug delivery and telemedicine should be promoted to maintain control of mental health and life quality during the pandemic.